The Use of Game-based methods for teaching lawdisciplines in a technical university - Ageeva V. V. Vera Valentinovna; Tatarintseva I. A. Inga Aleksandrovna; Dedkova T. A. Tatiana Anatolievna; Galkina P, V. Polina Vadimovna (2016, 2016)
Title screen